Characteristics of antipsychotic drug‐induced hypothermia in psychogeriatric inpatients. (17th September 2021) - Kamp, Daniel; Paschali, Myrella; Bouanane, Annabelle; Christl, Julia; Supprian, Tillmann; Meisenzahl‐Lechner, Eva; Kojda, Georg; Lange‐Asschenfeldt, Christian
Abstract: Objective: Hypothermia is a potentially lethal adverse reaction to typical and atypical antipsychotic drugs (APD). Among predisposing factors are advanced age and comorbid somatic diseases. The aim of this study was to assess the incidence of hypothermia and quantify risk factors. Method: Charts of N  = 3002 psychogeriatric inpatients were screened for incidence of hypothermia (body core temperature <35.0°C). The frequency of hypothermia was compared between patients treated with versus without APD and, within the sample of APD‐treated patients, for (1) specific APD, (2) sex, (3) main diagnosis, and (4) age. Results: N  = 54 cases (2.6%) of hypothermia occurred in APD‐treated patients and 12 cases (1.3%) in non‐APD‐treated patients ( p  = 0.024). In APD‐treated patients, only male sex ( p  = 0.038) and pipamperone were associated with a higher incidence of hypothermia ( p  = 0.0017). Whereas the main diagnosis delirium showed a trend to significance, age did not correlate with hypothermia. Conclusion: Medication with pipamperone was associated with an increased risk of hypothermia. The advanced age of our sample might as well explain the high incidence of hypothermia within our sample and the failure to detect high age as a risk factor due to a ceiling effect.